2004
DOI: 10.1080/08037050410016492
|View full text |Cite
|
Sign up to set email alerts
|

The coexistence of acute aortic dissection with autosomal dominant polycystic kidney disease - description of two hypertensive patients

Abstract: Aortic dissection is a rare but potentially disastrous complication, and clinicians should always consider this when dealing with patients with ADPKD who present with chest pain or collapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The study selection process is represented in Figure 3. We report data from 27 cases ( Table 1) of ADPKD patients with AD, of which 25 were previously identified from the literature [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and two from our clinical experience. A schematic representation of age, hypertension and CKD stage distribution in the study population is reported in the Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study selection process is represented in Figure 3. We report data from 27 cases ( Table 1) of ADPKD patients with AD, of which 25 were previously identified from the literature [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and two from our clinical experience. A schematic representation of age, hypertension and CKD stage distribution in the study population is reported in the Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…However, additional manifestations are often described, including: intracranial, coronary and other arterial aneurysms, arterial dolichoectasias, aortic or cervicocephalic arteries dissections, and heart valve diseases . Although ADPKD‐AD association has been previously reported, only few cases are available in the literature and a systematic review has never been made. We report two cases of AD in ADPKD patients from our experience and perform a systematic analysis of the literature.…”
mentioning
confidence: 99%
“…PKD1 may also have a role in the development and function in endothelial- and mesenchymal-derived cells. PKD1 mutations lead to vascular (intracranial and aortic aneurysms) [8], [9], [10], [11] and lung (bronchiectasis) abnormalities [12]. PKD1 and PKD2 are required for placental development [13].…”
Section: Introductionmentioning
confidence: 99%
“…3,7,8) Among the vascular manifestations of ADPKD, relatively few cases of thoracic aortic dissection have been published in English literature, [8][9][10][11][12][13][14][15][16][17] when compared with reports of intracranial aneurysms, which are well-established extrarenal manifestations of ADPKD and occur in approximately 6% of patients without a family history of aneurysms and in 16% of those with such a family history. 18) Marfan syndrome is a well-known systemic connective tissue disorder that leads to life-threatening cardiovascular complications.…”
Section: )mentioning
confidence: 99%
“…11) Some authors have warned the medical community of the presence of aortic dissection in patients with ADPKD and concomitant hypertension. 10,11,13) Through these reports, physicians must pay attention to the possibility of devastating entity behind ADPKD.…”
Section: )mentioning
confidence: 99%